Highly tumoricidal efficiency of non-oxidized MXene-Ti3C2Tx quantum dots on human uveal melanoma - Zhang, Huankai; Li, Xuesong; You, Pan; Song, Xian; Fan, Qian; Tao, Xutang; Qu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Uveal melanoma (UM) is a highly malignant intraocular tumor with poor prognosis. Current topical ophthalmic therapies purpose to conserve the eye and useful vision. Due to the risks and limited clinical benefits, the topical treatments of UM remain challenging and complex. In this study, newly developed non-oxidized MXene-Ti3C2Tx quantum dots (NMQDs-Ti3C2Tx) are proposed for UM treatment. Surprisingly, NMQDs-Ti3C2Tx shows significant tumor-killing effects on UM cells even using a small dosage (at 25μg mL−1) and causes severe necrosis near the injection site on the xenograft UM tumor model. Moreover, NMQDs-Ti3C2Tx exhibits excellent biocompatibility with normal retina pigment epithelium (RPE) cells and does not cause any damage in C57BL/6 mice eyes. Mechanistically, NMQDs-Ti3C2Tx inhibits the proliferation, invasion, and migration of UM cells via its desirable reactive oxygen species (ROS) generation ability, which causes lipid peroxidation and mitophagy, triggering cell ferroptosis. Furthermore, NMQDs-Ti3C2Tx is detected accumulating in autolysosomes which exacerbates cell death. This work provides new lights on the topical treatment of UM.